Answering questions on call: Pediatric resident physicians' use of handoffs and other resources. Issue 6 (16th April 2013) - McSweeney, Maireade E.; Landrigan, Christopher P.; Jiang, Hongyu; Starmer, Amy; Lightdale, Jenifer R.
<x xml:space="preserve">Abstract</x> BACKGROUND Little is known in the literature about the types of questions being asked of on‐call housestaff and the resources used to provide answers. OBJECTIVE To characterize questions being asked of pediatric interns on call and evaluate their use of written handoffs, verbal handoffs, and other resources. DESIGN/METHODS Prospective direct observational study. SETTING Inpatient wards at an academic tertiary care children's hospital. PARTICIPANTS Pediatric interns. RESULTS Trainees were asked 2.6 questions/hour (interquartile range: 1.4–4.7); most involved medications (28%), general care plans (27%), diagnostic tests/procedures (22%), diet/fluids (15%), and physical exams (9%). Interns reported using information provided in written or verbal handoffs to answer 32.6% questions (written 7.3%; verbal 25.3%). Other resources utilized included general medical knowledge, the medical record, and parental report. Questions pertaining to diet/fluids were associated with increased written handoff use (odds ratio [OR]: 3.64, 95% confidence interval [CI]: 1.51–8.76), whereas having worked more consecutive nights was associated with decreased written handoff use (OR: 0.29, 95% CI: 0.09–0.93). Questions regarding general care plans (OR: 2.07, 95% CI: 1.13–3.78), those asked by clinical staff (OR: 1.95, 95% CI: 1.04–3.66), and questions asked of patients with longer lengths of stay (OR: 1.97, 95% CI: 1.02–3.80) were predictive of verbal handoff use. CONCLUSIONS Pediatric housestaff face frequent questions during overnight shifts and frequently use information received during handoffs to provide answers. A better understanding of how handoffs and other resources are utilized by housestaff could inform future targeted initiatives to improve trainees' access to key information at night. Journal of Hospital Medicine 2013;8:328–333. © 2013 Society of Hospital Medicine